Continuous flow synthesis of amines from the cascade reactions of nitriles and carbonyl-containing compounds promoted by Pt-modified titania catalysts. Issue 2 (13th December 2018) - Altuğ, Cevher; Muñoz-Batista, Mario J.; Rodríguez-Padrón, Daily; Balu, Alina M.; Romero, Antonio A.; Luque, Rafael
Abstract : A Pt-modified titania-based catalyst was successfully applied in the synthesis of amines employing several carbonyl containing molecules and nitriles. Abstract : The effective design of an active and stable catalytic system was performed by a simple modification of a commercial titania with a low platinum loading. The prepared material was fully characterized by XRD, XPS, N2 adsorption–desorption measurements, ICP-MS, TEM and SEM analyses. Such techniques corroborated the successful incorporation of Pt onto the titania surface, without affecting its original structure, morphology and chemical nature. The obtained TiO2 –Pt catalyst was effectively applied in several continuous flow reactions between nitriles and carbonyl containing compounds for amine preparation. Remarkably, conversion of levulinic acid, a biomass derived molecule, was achieved with outstanding conversion (87%) and selectivity (80%) to 1-ethyl-5-methylpyrrolidin-2-one. The catalytic system demonstrated a high stability through 120 min of reaction. Moreover, the effect of the nitrile was investigated by performing the reaction with benzonitrile and ethylcyanoacetate. The TiO2 –Pt catalyst was also tested in the conversion of benzaldehyde, displaying remarkable results. The influence of substitution in the aromatic ring was investigated using p -nitro-benzaldehyde and p -chloro-benzaldehyde.